Beyond the Classroom: Total Quality Management and Digital Innovation in Education - Rada, Rada; Dewi, Indah Kusuma; Mashar, Ali; Alamsyah, Riko (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aims to analyze the implementation of digital education innovation based on Total Quality Management (TQM) in Islamic Boarding Schools in the Bangka Belitung Islands. This study uses a qualitative approach with a case study design, where data is collected through interviews, observations, and documentation, then analyzed descriptively with the Interactive Analysis Model from Miles & Huberman, including data reduction, data display, and data verification. The study results indicate that the commitment of Islamic boarding school management is significant in providing adequate digital infrastructure for learning. Implementing TQM in Islamic boarding schools requires the involvement of all elements of the school, including managers, teachers, and students. Designing a digital-based curriculum that integrates local wisdom also plays a role in maintaining Islamic boarding school values while meeting the demands of technological developments. In addition, enhancing resource capacity, especially teachers, through technology training is the key to success in implementing digital media. Focusing on user satisfaction, both students and teachers, is also essential to ensure the success of digital learning. The implications of this study indicate that implementing digital-based TQM in Islamic boarding schools not only strengthens the quality of education but also introduces a technology-based approach relevant to the needs of the times without ignoring the traditional values of Islamic boarding schools.